The Phylodynamics of Seasonal Influenza A/H1N1pdm Virus in China Between 2009 and 2019 - Ma, Yingying; Liu, Kai; Yin, Yong; Qin, Jianru; Zhou, Yan-Heng; Yang, Juan; Li, Shenwei; Poon, Leo L. M.; Zhang, Chiyu (Frontiers in Microbiology, 2020)
Since its first introduction into China in 2009, influenza A/H1N1pdm virus has undergone a rapid expansion and replaced the classical seasonal A(H1N1) virus. To characterize the ongoing evolution and national transmission dynamics of this virus, we analyzed 335 complete genome, 1259 HA, and 1043 NA sequences of the A/H1N1pdm strains detected in China. We found that the dN/dS value and relative genetic diversity of the A/H1N1pdm virus experienced a decrease from 2009 to 2017, and then a rapid increase during 2018-2019. Importantly, elevated relative genetic diversity was observed in the A/H1N1pdm and the A/H3N2 viruses, as well as two lineages (Victoria and Yamagata) of influenza B virus during 2018-2019, suggesting the simultaneous changes of these viruses in terms of genetic diversity might be associated with the recent large outbreak of seasonal influenza epidemic in China during 2018-2019. Fifteen amino acid mutations were found to be fixed along the main trunks of both HA and NA phylogenetic trees, and some of them are located in the antigen binding site or the receptor binding site. A sequential accumulation of mutations relative to the 2009-vaccine strain was observed in the circulating A/H1N1pdm strains during 2009-2016, while a rapid accumulation of mutations relative to the 2015-vaccine strain appeared in the emerging variants in 2017 shortly after the release of the vaccine. Multiple introductions of the A/H1N1pdm lineages into China were observed during 2009-2019, and East China and South China were found to serve as two major epicenters responsible for the national migration of the virus. In summary, these data provide important insights into the understanding of the evolution, epidemiology and transmission of the A/H1N1pdm virus, and highlight the importance of strengthening influenza surveillance in East China and South China.